2D visualization on Malay documents / Sidi Bukhari Sidi Omar - Sidi Omar, Sidi Bukhari (2011)
Currently, browsing through web sites can only be done in a text form. Although there are some research has been made to browse in graphical form, it is not widely used. Hence, not many people know about it. If users browse through web sites that contains many Malay documents, then it would be in text form. Because of that, users cannot gain the overview of the relationship of those Malay documents. Hence, a prototype is built to overcome this problem. The Malay documents is collected and processed with cosine similarity technique to obtain the relationship between Malay documents. Then, the relationship is visualized where users can see the overview of the relationship of those Malay documents. The prototype was evaluated with usability questionnaire. Each question is then discussed and users agreed on some of it. Then it is concluded that users agreed that the prototype is much better than the linear system, the system that we compared to.